1085. Comparison of the Incidence of AKI in Vancomycin AUC Based Goal Trough Dosing vs. Traditional Trough Dosing in the Outpatient Setting. (4th December 2021) - Rees, Marissa; Bremmer, Derek N; Carr, Dustin R; Trienski, Tamara; Buchanan, Carley; White, Kara M
Abstract: Background: Recent changes to vancomycin guidelines recommend dosing by targeting an AUC of 400-600 in most patients, due to similar effectiveness and reduced rates of acute kidney injury (AKI). AKI was defined as an increase in serum creatinine of ≥ 0.5 mg/dl, a 50% increase in serum creatinine from baseline on two consecutive readings, or a decrease in creatinine clearance from 50% from baseline on two consecutive readings. The purpose of this study was to assess the incidence of AKI in patients receiving vancomycin dosed by AUC based trough goals and vancomycin dosed by traditional trough goals (15-20 mcg/mL) in the outpatient setting. Methods: This study was performed by retrospective chart review using the electronic health record. Patients receiving vancomycin outpatient as continuation of therapy after discharge from December 1, 2018 through March 24, 2021 were reviewed. The primary objective was incidence of AKI in patients receiving vancomycin outpatient with trough goals derived from patient specific AUC calculations compared to patients receiving vancomycin by traditional goal troughs. Secondary objectives included rate of treatment failure, average AUC estimated trough range, and number of regimen changes required. Results: There were a total of 65 patients in the traditional trough dosing group and 53 patients in the AUC trough dosing group. The incidence of AKI was higher in the traditional trough dosing group compared to the AUC trough group (23.1% vs 5.7%; p=0.01). There were no differences in incidence of treatment failure. The mean AUC estimated trough range was 11.4-16.9 mcg/mL. There were significantly less average regimen changes required in the AUC dosing group (1.64 vs 1.13; p=0.006). Patients receiving AUC trough dosing were 78% less likely to develop AKI as patients receiving traditional trough dosing (HR 0.221, 95%CI 0.051 – 0.968). Conclusion: There was a significantly lower incidence of AKI in patients receiving vancomycin dosed by AUC based troughs compared to traditional trough dosing. Continuing AUC trough based dosing for vancomycin in the outpatient setting is convenient and may lead to reduced rates of AKI. Disclosures: Dustin R. Carr, PharmD, BCPS, BCIDP, AAHIVP, Merck (Speaker's Bureau)